Caracterização morfológica, etnografia e potencialidade para uso ornamental de variedades crioulas de abóboras do Rio Grande do Sul. - Fischer, Síntia Zitzke (2012)
Family farmers in Rio Grande do Sul State, Brazil, grow several landraces of squashes and pumpkins, integrated in their production systems, which represent a wide genetic and cultural heritage. These farmers are responsible by their own selections of fruit according to their preferences: pumpkins for consumption in food, to prepare specific dishes, or ornamental pumpkins. These landraces have great variability in color, shape and texture of fruit, which can be exploited as a decorative element. This thesis aims to contribute to the knowledge of pumpkins ornamental landraces cultivated by farmers in Rio Grande do Sul State. The data were presented and discussed in four articles. Accessions of pumpkins ornamental landraces from the Cucurbitaceae Active Germplasm Bank of Embrapa Temperate Agriculture were identified and presented in the Article 1. The accessions were grown and fruits were morphologically characterized. This characterization revealed a great genetic diversity. After identification of accessions with the possibility for ornamental use, interviews were conducted with farmers donors of these accessions in order to make a survey of popular knowledge associated with use and cultivation of these landraces. This ethnobotanical survey, discussed in Article 2, showed that farmers have a relationship of affection with the varieties grown by them. The acceptance of ornamental pumpkins by consumers and their perception of the aesthetic attributes was discussed in the Article 3. Such information is important since it allows access the market preference with respect to various attributes (in this case, shape, color and texture of fruit), and thus direct future selections in breeding programs. Information about the cultivation of ornamental pumpkins are also fundamental to the market, both for those who will produce to market or for own consumption. The presentation of possibilities to use ornamental pumpkins, likewise, it is important to entice the consumer. Thus, in the Article 4, the management for the cultivation of ornamental pumpkins and various possibilities of use (during cultivation of the plant, beautifying the garden, and for fruits after harvestingt, used in different decorations) was described.